2011
DOI: 10.1002/cmdc.201100144
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Adamantyl Heterocyclic Ketones as Potent 11β‐Hydroxysteroid Dehydrogenase Type 1 Inhibitors

Abstract: 11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1) plays a key role in converting intracellular cortisone to physiologically active cortisol, which is implicated in the development of several phenotypes of metabolic syndrome. Inhibition of 11β-HSD1 activity with selective inhibitors has beneficial effects on various conditions, including diabetes, dyslipidemia and obesity, and therefore constitutes a promising strategy to discover novel therapies for metabolic and cardiovascular diseases. A series of novel ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…20 We therefore pursued the synthesis of compounds 19-30, which have the phenyl ethanone moiety tethered to the thiadiazole through either a sulphoxide or sulphone linker ( Table 2). The bicyclic analogues 19 and 20 both show reduced activity when measured at 1 mM, as does the para-methoxy compound 21 with a sulphoxide linker.…”
Section: Structure-activity Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…20 We therefore pursued the synthesis of compounds 19-30, which have the phenyl ethanone moiety tethered to the thiadiazole through either a sulphoxide or sulphone linker ( Table 2). The bicyclic analogues 19 and 20 both show reduced activity when measured at 1 mM, as does the para-methoxy compound 21 with a sulphoxide linker.…”
Section: Structure-activity Relationshipmentioning
confidence: 99%
“…[19][20][21] We previously reported that compounds 1 and 2 ( Fig. 1) are highly active 11b-HSD1 inhibitors when tested on an HEK293 cell line transfected with the human 11b-HSD1 gene.…”
Section: Introductionmentioning
confidence: 98%
“…The inhibitory activities of compounds 1-4 were measured in HEK293 cells transfected with the human HSD11B1 gene. [38,[41][42] Scheme 1. Synthesis of the adamantyl ethanone compounds (for Ar, see Tables 1-3).…”
Section: Chemistrymentioning
confidence: 99%
“…[39,40] We previously identified some adamantyl ethanone derivatives as potent inhibitors of human 11b-HSD1. [41,42] Compounds 2-4 exhibit high inhibitory activity with nanomolar IC 50 values when examined in a HEK293 cell line stably transfected with the HSD11B1 gene ( Figure 1). These compounds also show reasonable metabolic stability when incubated with human liver microsomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation